Control on carbonate reservoir properties along a shallowing-upward sequence: The middle oxfordian jura inner platform predictive model. (April 2023) - Richard, J.; Sizun, J.-P.
Abstract: The study of the Bonnevaux section from the Middle Oxfordian Jura inner platform (France) highlights that a shallowing-upward sequence showing a large variability of original microfacies linked to various depositional environments (open sea to lagoon) can be exclusively composed of microporous limestones. A spatial evolution of reservoir qualities and transport properties of these microporous limestones is recognized at the platform scale: a correlated increase in total porosity (from 2.8 to 21.3%) and permeability (from 0.0001 to 16 mD) and a decrease in trapped porosity (from 100 to ∼50%) is observed from the upper offshore to the back-shoal lagoon environments. The increase in permeability observed at the platform scale is correlated with an evolution of the unimodal distribution of pore access radii and an increase in threshold radius (from 0.033 to 0.570 μm). It results from a diachronism in the control of meteoric pore-fluid flows by the microporosity (vs macroporosity) during the burial diagenesis. A later control of meteoric pore-fluid flows by the microporosity related to differences in cementation (1) reduces the fluid-rock interactions in the micrite areas and consequently promotes open fabrics with larger pore access radii and (2) allows to preserve larger pore access radii in the intercrystalline pore network of cements. In the case of reservoir qualities, this later control (1) promotes a higher total porosity in the micrite areas in relation with more open fabrics and (2) allows to preserve larger pore access inducing a lower trapped porosity. The macroporosity can played a key role when the blocky cementation of the pore space is partial. This study also reveals that a submarine lithification can prevent the petrophysical impact of a pore-fluid meteoric input during the burial diagenesis. Highlights: Control on carbonate reservoir properties along a shallowing-upward sequence. A shallowing-upward sequence can be exclusively composed of microporous limestones. A spatial evolution of reservoir properties is observed at the platform scale. The control of meteoric pore fluid flows by the microporosity plays a key role. The submarine lithification can prevent the petrophysical impact of meteoric inputs.